Fiber Surface and Paper Technical Properties of Eucalyptus globulus and Eucalyptus nitens Pulps after Modified Cooking and Bleaching - Rudine Antes; Olli Pekka Joutsimo (BioResources, 2015)
The SuperBatch™(SB), CompactCooking™(CC), and Lo-Solids™ (LS) modified cooking methods were evaluated relative to the cell wall surface and paper technical properties of bleached Eucalyptus globulus and Eucalyptus nitens. E. globulus pulps presented higher screened yield and brightness than E. nitens, which needed higher H-factor to reach a kappa number target. Independently of the cooking method or species, all the samples consumed similar amounts of ClO2 to reach a brightness of 90% ISO. E. nitens pulps showed lower carbohydrates and higher extractives content on the fiber surface, regardless of the cooking method. E. nitens presented slightly higher surface charge of the bleached pulps. Surface charges of CC and LS pulps were higher independently of cooked Eucalyptus species. Water retention value (WRV) for E. nitens pulps were higher than for E. globulus. No differences were observed in refinability of different cooking methods, however E. nitens pulps showed higher tensile and lower bulk compared to E. globulus. E nitens presented a thinner fiber cell wall than E. globulus. This seems to be more relevant for paper technical properties and WRV than fiber charge or surface composition. No correlation between surface composition, fiber surface properties, and paper technical properties among the cooking methods could be determined.